Role of Murine Complement Component C5 in Acute in Vivo Infection by Pathogenic Leptospira interrogans - de Castro, Íris A.; Bavia, Lorena; Fraga, Tatiana R.; Amano, Mariane T.; Breda, Leandro C. D.; Granados-Martinez, Adriana P.; da Silva, Ana M. G.; Vasconcellos, Silvio A.; Isaac, Lourdes (Frontiers in Cellular and Infection Microbiology, 2018)
Leptospirosis is considered one of the most important zoonosis worldwide. The activation of the Complement System is important to control dissemination of several pathogens in the host. Only a few studies have employed murine models to investigate leptospiral infection and our aim in this work was to investigate the role of murine C5 during in vivo infection, comparing wild type C57BL/6 (B6 C5+/+) and congenic C57BL/6 (B6 C5-/-, C5 deficient) mice during the first days of infection. All animals from both groups survived for at least 8 days post-infection with pathogenic Leptospira interrogans serovar Kennewicki strain Fromm (LPF). At the third day of infection, we observed greater numbers of LPF in the liver of B6 C5-/- mice when compared to B6 C5+/+ mice. Later, on the sixth day of infection, the LPF population fell to undetectable levels in the livers of both groups of mice. On the third day, the inflammatory score was higher in the liver of B6 C5+/+ mice than in B6 C5-/- mice, and returned to normal on the sixth day of infection in both groups. No significant histopathological differences were observed in the lung, kidney and spleen from both infected B6 C5+/+ than B6 C5-/- mice. Likewise, the total number of circulating leukocytes was not affected by the absence of C5. The liver levels of IL-10 on the sixth day of infection was lower in the absence of C5 when compared to wild type mice. No significant differences were observed in the levels of several inflammatory cytokines when B6 C5+/+ and B6 C5-/- were compared. In conclusion, C5 may contribute to the direct killing of LPF in the first days of infection in C57BL/6 mice. On the other hand, other effector immune mechanisms probably compensate Complement impairment since the mice survival was not affected by the absence of C5 and its activated fragments, at least in the early stage of this infection.